Metal-insulator transition in Nd1-xEuxNiO 3 compounds - Escote, M. T. [UNESP]; Barbeta, V. B.; Jardim, R. F.; Campo, J. (IOP Publishing, 2006)
Polycrystalline Nd1-xEuxNiO3 (0≤x≤0.5) compounds were synthesized in order to investigate the character of the metal-insulator (MI) phase transition in this series. Samples were prepared through the sol-gel route and subjected to heat treatments at ∼1000 °C under oxygen pressures as high as 80bar. X-ray diffraction (XRD) and neutron powder diffraction (NPD), electrical resistivity ρ(T), and magnetization M(T) measurements were performed on these compounds. The NPD and XRD results indicated that the samples crystallize in an orthorhombic distorted perovskite structure, space group Pbnm. The analysis of the structural parameters revealed a sudden and small expansion of ∼0.2% of the unit cell volume when electronic localization occurs. This expansion was attributed to a small increase of ∼0.003 of the average Ni-O distance and a simultaneous decrease of ∼-0.5° of the Ni-O-Ni superexchange angle. The ρ(T) measurements revealed a MI transition occurring at temperatures ranging from TMI∼193 to 336K for samples with x ≤ 0 and 0.50, respectively. These measurements also show a large thermal hysteresis in NdNiO3 during heating and cooling processes, suggesting a first-order character of the phase transition at TMI. The width of this thermal hysteresis was found to decrease appreciably for the sample Nd 0.7Eu0.3NiO3. The results indicate that cation disorder associated with increasing substitution of Nd by Eu is responsible for changing the first-order character of the transition in NdNiO3. © 2006 IOP Publishing Ltd.
Keywords: Electric resistance; Europium compounds; Heat treatment; Magnetization; Metal insulator transition; Niobium compounds; Phase transitions; Polycrystalline materials; Sol-gels; X ray diffraction analysis; Electronic localization; Metal-insulator (MI) phase transition; Neutron powder diffraction (NPD); Orthorhombic distorted perovskite; Neodymium compounds